Avaliação da eficiência de sistemas de pré-tratamento de água utilizando filtros preenchidos com diferentes materiais e características granulométricas - Poncio, Tiago Onuczak (2023)
Pre-filtration systems are very important to adjust raw water within the parameters required by legislation so that it is possible to use it for slow filtration as a form of treatment. The present study aimed to analyze the efficiency of water pre-treatment systems using different materials with a filtering layer of different particle sizes. The 6 systems were constituted using a support layer, followed by a single layer of anthracite coal and sand with granulometries of 0.2 mm, 0.4 mm and 0.6 mm for both materials. Both systems were operated with a filtration rate of 4 m³/m².day. At each career end, a superficial cleaning was carried out, 5 cm above, of the filtering layer. Each one of the pre-filters presented a different operation time, due to the deactivation periods for cleaning, varying between 118 and 136 days, except for the system composed of anthracite coal with a D10 of 0.6 mm, which did not present career closure. filtration, being operated for 137 days. The system that presented the best performance for removing turbidity and apparent color was the one composed of anthracite coal with a granulometry of 0.4 mm of effective diameter. For the parameters of true color and solids in suspension, the pre-filter with a filtering layer composed of anthracite coal of D10 0.2 mm proved to be more efficient. The analysis carried out on the filtering material after slicing, at the end of the system operation, detected the presence of E. Coli in the superficial 2 cm of the draining layer in the systems composed of granulometry of 0.4 mm and 0.6 mm of anthracite coal. The presence of general microorganisms was observed in all systems, and the systems composed of 0.6 mm anthracite and 0.4 mm sand were identified in the first 2 cm of depth. All systems showed the presence of heterotrophic bacteria in all layers, with the highest concentration recorded in the draining system composed of charcoal with a granulometry of 0.2 mm. The results presented did not follow the filtration theory, which may be due to the greater number of career ends in systems composed of smaller granulometries, which caused pore opening and, consequently, greater percolation of particulate material, as well as bacteria and microorganisms , at greater depths. The detection of microorganisms in the system that did not show career closure may be related to the uniformity of the grains associated with the intragranular velocity during the operation of the system. The analyzed pre-filters can be used to prepare water for use in slow filtration systems, allowing the use of smaller areas for water collection, as well as reducing costs for water treatment.